Awareness of Diagnosing Autism Spectrum Disorders and Social (Pragmatic) Communication Disorder among Student Teachers According to Some Variables (Journal Of Educational and Psychological Researches, 2022)
The research aims to identify the level of awareness of student teachers in the behavioral disorders and autism specialization about the diagnosing Autism Spectrum Disorder and Social (Pragmatic) Communication Disorder according to some variables. The study was conducted on a sample of (113) student teachers. The researcher employed the awareness scale of a teacher-screening questionnaire for autism spectrum disorder and social pragmatic communication disorder. The results showed that the average of teachers in the total degree of awareness of autism spectrum disorder and social communication have recorded a moderate degree. As for the awareness of autism spectrum disorder was high. Then, the awareness of social communication disorder was medium. The result also showed that there is a statistically significant difference at the level of (0.05) in favor of the training course attendance. There is a significant regression in awareness of the disorders of the autism spectrum and social communication according to the variables.